What do we know about sex? Poking the Squid: What We Can Learn from Animal Sex Perrin Roosevelt Ireland Norton, 2026. 272 pp. On the Origin of Sex: The Weird and Wonderful Science of Reproduction Lixing Sun Basic Books, 2026. 368 pp. - Nathan H. Lents (Science, 2026)
It depends on whom you ask